PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DAN TURNOVER INTENTION - Agi Syarif Hidayat (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The high level of employee turnover in the marketing department at PT. Toyamilindo indicates low organizational commitment and high turnover intention. The purpose of this study is to determine the effect of job satisfaction on organizational commitment and turnover intention. Quantitative methods are used in this study. Population is the employees of marketing department at PT. Toyamilindo with 50 people. Sampling technique used is sampling saturated with the number of samples of 50 people. Data collection technique uses questionnaires and regression analysis. Finding on the research results shows that there are positive and significant influence of job satisfaction on organizational commitment and negative and significant influence of job satisfaction on turnover intention, and also the influence of organizational commitment on work satisfaction to turnover intention. The managerial implications of corporate leaders must improve employee work satisfaction, especially in terms of salary.